Management of multidrug-resistant enterococcal infections (2010)
Enterococci are organisms with a remarkable ability to adapt to the environment and acquire antibiotic resistance determinants. The evolution of antimicrobial resistance in these organisms poses enormous challenges for clinicians when faced with patients affected with severe infections. The increased prevalence and dissemination of multidrug-resistant Enterococcus faecium worldwide has resulted in a major decrease in therapeutic options because the majority of E. faecium isolates are now resistant to ampicillin and vancomycin, and exhibit high-level resistance to aminoglycosides, which are three of the traditionally most useful anti-enterococcal antibiotics. Newer antibiotics such as linezolid, daptomycin and tigecycline have good in vitro activity against enterococcal isolates, although their clinical use may be limited in certain clinical scenarios as a result of reduced rates of success, possible underdosing for enterococci and low serum levels, respectively, and also by the emergence of resistance. The experimental agent oritavancin may offer some hope for the treatment of vancomycin-resistant enterococci but clinical data are still lacking. Thus, optimal therapies for the treatment of multidrug-resistant enterococcal infections continue to be based on empirical observations and extrapolations from in vitro and animal data. Clinical studies evaluating new strategies, including combination therapies, to treat severe vancomycin-resistant E. faecium infections are urgently needed.